GENE CONSTRUCTION AND PROTEIN CHARACTERIZATION OF POLYETHYLENE TEREPHTHALATE HYDROLASE (PETASE) IN ESCHERICHIA COLI BL21 (DE3) - NATHANAEL IMAN , MARVIN
Polyethylene terephthalate (PET) is one of the most produced and consumed synthetic polymers. Every year, around 50 million tons of PET-based products are manufactured, most prominent of those are the very versatile and durable plastic-based products. Ironically, the durability and strength of PET-based products also contribute to its great resistance against bio-degradation. Due to this resistance, PET wastes are heavily accumulated all around the world, polluting the environment. In 2016, Japanese researchers discovered a novel PET-degrading enzyme from the bacteria Ideonella sakaiensis. This PET-degrading enzyme is later known as PET hydrolase (PETase). PETase is a very prospective solution against PET pollution. In order to utilize its potentials, various characterizations of the enzyme must be first performed. In this research, a PETase expression system was constructed using Escherichia coli BL21 (DE3) as host. In the process, various optimizations to the native sequence of PETase were performed in order for E. coli BL21 (DE3) to be able to express this enzyme optimally. The optimizations included codon optimization, addition of suitable constitutive promoter, ribosomal binding site, and terminator. Following the construction of the expression system, the PETase expression was characterized using SDS-PAGE analysis. The results showed that 44,38% of PETase was expressed extracellularly, while the remaining 55,62% was stuck in the intracellular space. The activity of the expressed enzyme was further assayed using p-nitrophenol butyrate-based colorimetric techniques. A response surface methodology (RSM)-based modeling of the enzyme activity in various pH and temperatures was then developed. Based on the model, optimal PETase activity was predicted to happen at 38.8Ã‚Â°C and the pH of 7.7. The constructed expression system as well as its characterization could be used to help develop a PETase-based remediation system.